Психологиялық пәндері оқытуда жобалау ic-әрекетін қолданудың тиімділігі - Молдахметова, Г.М. (My University, 2016)
The article is dedicated to speculation of problems of efficiency, opportunitu and practical usage of project working in teaching psychological subject. In the article discovered the meanings of notions «project», «project method» and «project work». The main feature of usage of project work in educating process characterized bu the author.
Keywords: project; project method; project work